Valence XPS structure and chemical bond in Cs2UO2Cl4 - Teterin Yury A.; Maslakov Konstantin I.; Ryzhkov Mikhail V.; Teterin Anton Yu.; Ivanov Kirill E.; Kalmykov Stepan N.; Petrov Vladimir G.; Suglobov Dmitry N. (Nuclear Technology and Radiation Protection, 2016)
Quantitative analysis was done of the valence electrons X-ray photoelectron spectra structure in the binding energy (BE) range of 0 eV to ~35 eV for crystalline dicaesium tetrachloro-dioxouranium (VI) (Cs2UO2Cl4). This compound contains the uranyl group UO2. The BE and structure of the core electronic shells (~35 eV-1250 eV), as well as the relativistic discrete variation calculation results for the UO2Cl4(D4h) cluster reflecting U close environment in Cs2UO2Cl4 were taken into account. The experimental data show that many-body effects due to the presence of cesium and chlorine contribute to the outer valence (0-~15 eV BE) spectral structure much less than to the inner valence (~15 eV-~35 eV BE) one. The filled U5f electronic states were theoretically calculated and experimentally confirmed to be present in the valence band of Cs2UO2Cl4. It corroborates the suggestion on the direct participation of the U5f electrons in the chemical bond. Electrons of the U6p atomic orbitals participate in formation of both the inner (IVMO) and the outer (OVMO) valence molecular orbitals (bands). The filled U6p and the O2s, Cl3s electronic shells were found to make the largest contributions to the IVMO formation. The molecular orbitals composition and the sequence order in the binding energy range 0 eV-~35 eV in the UO2Cl4 cluster were established. The experimental and theoretical data allowed a quantitative molecular orbitals scheme for the UO2Cl4 cluster in the BE range 0-~35 eV, which is fundamental for both understanding the chemical bond nature in Cs2UO2Cl4 and the interpretation of other X-ray spectra of Cs2UO2Cl4. The contributions to the chemical binding for the UO2Cl4 cluster were evaluated to be: the OVMO contribution - 76%, and the IVMO contribution - 24 %.